2022
DOI: 10.1186/s13054-022-03907-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analysis of the host response reveals prognostic and pathogen-driven immune subtypes among adults with sepsis in Uganda

Abstract: Background The global burden of sepsis is concentrated in sub-Saharan Africa, where severe infections disproportionately affect young, HIV-infected adults and high-burden pathogens are unique. In this context, poor understanding of sepsis immunopathology represents a crucial barrier to development of locally-effective treatment strategies. We sought to determine inter-individual immunologic heterogeneity among adults hospitalized with sepsis in a sub-Saharan African setting, and characterize as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Secondary outcomes included a composite measure of in-hospital outcome (death in-hospital or transfer to Uganda's national referral hospital due to progressive severity of illness) and functional status at discharge (among patients who survived and were not transferred). Further details of the RESERVE-U study and study site capacity have been published and are summarized in the supplement [8,9]. Among adults enrolled in the RESERVE-U study, we first determined the impact of HIV on infecting pathogens, organ dysfunction, and in-hospital and 30day outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes included a composite measure of in-hospital outcome (death in-hospital or transfer to Uganda's national referral hospital due to progressive severity of illness) and functional status at discharge (among patients who survived and were not transferred). Further details of the RESERVE-U study and study site capacity have been published and are summarized in the supplement [8,9]. Among adults enrolled in the RESERVE-U study, we first determined the impact of HIV on infecting pathogens, organ dysfunction, and in-hospital and 30day outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…After successful prospective validation, both the UVA score and the amalgamated qSOFA could be used clinically to identify patients at risk for in-hospital death, which could be evaluated in a cluster randomized trial to determine whether identification of mortality risk leads to improved outcomes in different clinical settings. The UVA score has been used by others to control for severity of illness at admission in observational clinical studies and it could also be used for risk stratification in interventional studies [ 14 , 15 ]. For example, since steroid therapy for COVID-19 is based on severity of illness, the UVA score might be a useful indicator for steroid therapy in resource limited settings, which would need to be tested prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…In serum samples collected at RESERVE-U enrollment, we quantitated, using Luminex immunoassays (Luminex, Austin, TX), 14 soluble immune mediators reflective of immunopathological domains that may contribute to infection-related organ dysfunction, including among patients with severe HIV/TB. 3,13,[15][16][17][18] ). From whole-blood samples collected in PAXgene blood RNA tubes from a consecutive subset of patients, RNA was isolated and purified using PAXgene blood RNA kits (Qiagen, Hilden, Germany), after which RNA sequencing libraries were prepared using the NEBNext Ultra RNA Library Prep Kit (NEB, Ipswich, MA).…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Patients were included in the parent RESERVE-U study if they fulfilled the following criteria: (1) age $18 years, (2) reported a history of fever or had a recorded axillary temperature of $37.5°C, (3) had clinical illness severe enough to warrant admission to hospital, and (4) were able to provide informed consent or had a surrogate available to do so. 13,14 Patients were excluded if they presented after trauma or were admitted to a nonmedical ward. During the study period, all admissions to the medical wards were screened for eligibility by study staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation